PRODUCT QUALITY, LIFESTYLE, AND SOCIAL MEDIA MARKETING INCREASE PURCHASE DECISION THROUGH BRAND TRUST - Faradila, Firda; Silitonga, Parlagutan (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research aims to identify product quality, lifestyle, and social media marketing to increase purchasing decisions through brand trust in Sushi Hiro. Product quality, lifestyle, and social media marketing were the independent variables. Meanwhile, the dependent variable used in the research is brand trust and purchase decisions. This study involved 244 respondents who were collected using the distribution of questionnaires using the accidental sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of Smart-PLS software. The results of this study show that there is a significant influence between product quality on brand trust and purchase decisions. Then lifestyle has a significant effect on brand trust and purchase decisions. In addition, social media marketing also has a significant influence on brand trust and purchase decisions. Meanwhile, the hypothesis of brand trust against the purchase decision was rejected. Indirect influence testing shows that it acts as a mediator in the relationship between product quality, lifestyle, and social media marketing. Keywords: Product Quality; Lifestyle; Social Media Marketing ;Brand Trust; Purchase Decisions